1984
DOI: 10.21273/hortsci.19.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Of Tolerance To Water Stress

Abstract: Water availability is one of the principal environmental limitations of crop productivity throughout the world. The water deficits, which are a consequence of either continuous or transitory periods of drought, cause significant yield reductions on presently cultivated land, and greatly restrict the cultivation of crops on over one-third of the earth’s land surface considered to be arid or semiarid (25). These restrictions on yield potential are rapidly becom ing of great concern in the face of the food demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…The water potential gradient between the cells and surrounding nutrient medium caused by PEG results in cell dehydration. (Hasegawa et al 1984). Increasing PEG concentration was associated with a progressive reduction in water content of date palm callus (Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 89%
See 1 more Smart Citation
“…The water potential gradient between the cells and surrounding nutrient medium caused by PEG results in cell dehydration. (Hasegawa et al 1984). Increasing PEG concentration was associated with a progressive reduction in water content of date palm callus (Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 89%
“…Undifferentiated cells and callus cultures eliminate complications associated with genetic and morphological variability inherent to different tissues in whole plants. Moreover, cell culture systems eliminate all responses associated with water stress except those operative at the cellular level (Hasegawa et al 1984, Newton et al 1989). These studies involved the simulation of the effect of water stress by augmenting the culture media with polyethylene glycol (PEG) which induces osmoregulation through the accumulation of solutes such as proline.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Ainsi, la diminution de l'indice foliaire, qui a pour but de réduire la quantité d'eau perdue par la plante, la protégeant ainsi contre la déshydratation [10][11][12][13] La corrélation observée entre la diminution du rendement en grain et la diminution de l'indice foliaire, est la conséquence, comme l'ont révélé plusieurs auteurs, de la réponse des glycophytes au stress salin par une réduction de la croissance [23,24].…”
Section: Variation Du Rendement En Grainsunclassified
“…Cette réponse varie considérablement en fonction du genre, de l'espèce et même de l'écotype ou de la variété [1,[7][8][9]. La diminution de la croissance est une réponse à la déshydratation ; elle contribue à la conservation des ressources en eau, ce qui permet la survie de la plante [10][11][12]. Chez la tomate, la diminution de la croissance n'est pas considérée comme une conséquence des perturbations osmotiques, mais comme une stratégie qui permet à la plante de limiter les pertes d'eau par transpiration et de maintenir ainsi une bonne valeur de l'efficacité d'utilisation de l'eau [13].…”
Section: Introductionunclassified
“…In vitro techniques are indispensable for developing selected stress-tolerant varieties (Jan et al 2018; Rao and Jabeen, 2013), and understanding defense mechanisms and drought effects on the plant cell scale. Hasegawa et al (1984) and Newton et al (1989) reported that using undifferentiated cells (callus) under controlled conditions allowed similar assessment against water stress effects by eliminating all other reactions. Previous works have focused on in vitro stress responses because the dissociated cells could acquire a similar behavior to intact-plant cells subjected to water stress conditions (Attree et al 1991).…”
Section: Introductionmentioning
confidence: 99%